Upaya Menumbuhkan Kreativitas Anak melalui Kegiatan Pembuatan Ecoprint di TK Dharma Wanita Garon Kawedanan Kabupaten Magetan - Faristiana, Andhita Risko; Sary, Ary Eka Muthiara; Fatimah, Fitri Ayu; Gunawan, Joni (Jurnal Pengabdian KOLABORATIF, 2025)
Although creativity plays a crucial role in children's development, observations showed that eight out of twelve children had not yet reached their full potential. This was evident in their behavior, as they remained focused on the actions of their instructors and peers, were unable to identify different textures effectively, and lacked the skills to create various forms. Using natural dyes, ecoprinting produces patterns and colors on materials such as fabric, paper, leather, and ceramics. In addition to teaching the technical skill of the pounding method in ecoprinting, this community service project also provided botanical insights into leaves that produce clear and distinct prints when applied with the pounding technique. The project was conducted at Dharma Wanita Kindergarten Garon, located in Garon Village, Kawedanan Subdistrict. The objective of this activity was to enhance knowledge and foster creativity among children. The method employed was the Asset-Based Community Development (ABCD) approach. A total of 39 students from Dharma Wanita Kindergarten Garon participated in the program. All participants successfully created ecoprint designs on cloth bags, which they were able to take home afterward. This ecoprinting activity had a positive impact on stimulating creativity in children.
Keywords: children; creativity; ecoprint; pounding technique